Sciatic neuropathy and rhabdomyolysis after carbon monoxide intoxication: A case report. Issue 23 (June 2018) - Lee, Hyeok Dong; Lee, Sung Young; Cho, Young-Shin; Han, Seung Hoon; Park, Si-Bog; Lee, Kyu Hoon
Abstract: Rationale: Peripheral neuropathy is a rare complication of carbon monoxide intoxication. Peripheral neuropathy following carbon monoxide intoxication is known to completely recover within a few months. Patient concerns: A 40-year-old man complained of motor weakness and hypoesthesia of the right lower extremity with swelling of his right thigh after carbon monoxide intoxication resulting from a suicide attempt. Diagnoses: Following nerve conduction and electromyographic studies, the patient was diagnosed with sciatic neuropathy with severe axonopathy. Clinical and laboratory findings led to a diagnosis of rhabdomyolysis. Interventions: The patient was treated conservatively for rhabdomyolysis and underwent comprehensive rehabilitation for sciatic neuropathy during hospitalization. Outcomes: After discharge, he underwent serial follow-up tests with nerve conduction and electromyographic studies, which showed prolonged persistence of sciatic neuropathy; however, he showed significant improvement at his 26-month post-discharge follow-up. Lesson: Patients presenting with peripheral neuropathy secondary to carbon monoxide intoxication may show variable recovery periods; however, a favorable prognosis can be expected regardless of the concomitant occurrence of rhabdomyolysis and/or compartment syndrome.